WORKSHOP ENTREPRENEURSHIP TRAINING FOR STUDENTS AT SMK KARSA MULYA PALANGKA RAYA - Manalu, Sanggam Roy I.; Trissan, Whendy (Jurusan Pendidikan Teknologi dan Kejuruan, FKIP, Universitas Palangkaraya, 2019)
The creative economic development in city of Palangka Raya is really needed to deal with the challenges of economic growth that is relatively constant or even low after economic crises. High levels of poverty, unemployment and low industrial competitiveness to determine the direction of creative economic development for fulfilling instructions President Number 6 year 2009 is required efforts to develop the Creative Economy Entrepreneurship in the Framework of Enhancing Creative Economic Enterprises in the city of Palangka Raya. The purpose of this ibm is to increase student interest in entrepreneurship and to improve the economy quality and standard of living in the workshop area. Through this ibm activity will be offered a solution to the problems that have been formulated above. The approach is consisting of 1) Preparation Phase, 2) Assessment Phase, 3) Stage Alternative Planning of Programs or Activities, 4) Formulation of Action Plans Phase, 5) Implementation Stage, 6) Evaluation Phase, and 7) Termination Phase. The implementation of the IBM program is indeed carried out as an effort to empower in the field of entrepreneurship through entrepreneurship training activities that focus on business development program. Implementation methods using information technology and social media that will be carried out are (1) business management plate, (2) Production training, (3) administration, and (4) mentoring. All of these methods are an integral part of this IBM program. Workshop entrepreneurship training for vocational schools (mechanical and automotive major) is important to do in preparing students to enter the workforce after completing their education.